Exploring Self-Assessment of Speaking Skill by EFL High School Students - Wulida Wahidatul Masruria; Syafi’ul Anam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to know how self-assessment is implemented in the classroom and how students perceive using self-assessment to assess their speaking skills. This research study was used qualitative research conducted at the state Islamic senior high school level in Sorong. The results showed that most students thought that self-assessment was very helpful because it allowed them to know their strengths and weaknesses and improve their communication with the teacher. Moreover, the second results indicated that self-assessment assisted students in increasing their speaking self-efficacy (confidence and belief in their ability), self-regulation (awareness of research, time management, independence), and engagement. In conclusion, the teachers use self-assessment in English classes successfully. Keywords: EFL Learners, Self-assessment, Speaking Skill, Students' Responses